VD_FINDINFO Décision / 2024 / 148 vom 4. März 2024 - VD Tribunal cantonal (2024)
ADMISSION DE LA DEMANDE, DÉFENSE D'OFFICE, AVOCAT, ASSISTANCE JUDICIAIRE, INDEMNITÉEN GÉNÉRAL | 132 CPP (CH), 136 CPP (CH)